Lessons from the pandemic: why having a good understanding of occupational psychiatry is more important now than ever before. (October 2022) - Greenberg, Neil; Tarn, Mark; Tracy, Derek
Abstract : The COVID-19 pandemic has once again highlighted the need for all psychiatrists to have a good understanding of the bi-directional relationship between mental health and a person's ability to function well at work. Ensuring patients are able to work should be a key treatment outcome for all psychiatrists.